In vitro and split-faced placebo-controlled in vivo study on the skin rejuvenating effects of cream loaded with bioactive extract of Indigofera argentea Burm.f - Arshad, Tahreem; Shoaib Khan, Haji Muhammad; Khan, Kashif-ur-Rehman; Al-Roujayee, Abdulaziz S.; Mohany, Mohamed; Ahmad, Maqsood; Maryam, Sana; Akram, Muhammad Bilal; Shaukat, Hasnain; Khursheed, Umair; Aboul-Soud, Mourad A. M. (Frontiers in Pharmacology, 2024)
The bioactive extracts of traditional medicinal plants are rich in polyphenols and help to rejuvenate skin. The study was designed to assess the skin rejuvenating effects of a stable cream enriched with 4% Indigofera argentea (IaMe) extract. The quantity of polyphenols by spectrophotometric methods was TPC, 101.55±0.03 mg GAE/g and TFC; 77.14±0.13 mg QE/g, while HPLC-PDA revealed gallic acid; 4.91, chlorogenic acid 48.12, p-coumaric acid 0.43, and rutin 14.23 µg/ g. The significant results of biological activities were observed as DPPH; 81.81±0.05 %, tyrosinase; 72±0.23 % compared to ascorbic acid (92.43±0.03 %), and kojic acid (78.80±0.19 %) respectively. Moreover, the promising sun protection effects (SPF) of extract (20.53) and formulation (10.59) were observed. The active cream formulation (w/o emulsion) was developed with liquid paraffin, beeswax, IaMe extract, and ABIL EM 90, which was stable for 90 days as shown by various stability parameters. The rheological results demonstrated the active formulation's non-Newtonian and pseudo-plastic characteristics and nearly spherical globules by SEM. The IaMe loaded cream was further investigated on human trial subjects for skin rejuvenating effects and visualized in 3D skin images. Herein, the results were significant compared to placebo. IaMe formulation causes a substantial drop in skin melanin from -1.70% (2 weeks) to -10.8% (12 weeks). Furthermore, it showed a significant increase in skin moisture and elasticity index from 7.7 % to 39.15% and 2% to 30%, respectively. According to the findings, I. argentea extract has promising bioactivities and skin rejuvenating properties, rationalizing the traditional use and encouraging its exploitation for effective and economical cosmeceuticals.